If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + 2 = 4(x + 6) + -30 Reorder the terms: 2(-3 + x) + 2 = 4(x + 6) + -30 (-3 * 2 + x * 2) + 2 = 4(x + 6) + -30 (-6 + 2x) + 2 = 4(x + 6) + -30 Reorder the terms: -6 + 2 + 2x = 4(x + 6) + -30 Combine like terms: -6 + 2 = -4 -4 + 2x = 4(x + 6) + -30 Reorder the terms: -4 + 2x = 4(6 + x) + -30 -4 + 2x = (6 * 4 + x * 4) + -30 -4 + 2x = (24 + 4x) + -30 Reorder the terms: -4 + 2x = 24 + -30 + 4x Combine like terms: 24 + -30 = -6 -4 + 2x = -6 + 4x Solving -4 + 2x = -6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4 + 2x + -4x = -6 + 4x + -4x Combine like terms: 2x + -4x = -2x -4 + -2x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 -4 + -2x = -6 + 0 -4 + -2x = -6 Add '4' to each side of the equation. -4 + 4 + -2x = -6 + 4 Combine like terms: -4 + 4 = 0 0 + -2x = -6 + 4 -2x = -6 + 4 Combine like terms: -6 + 4 = -2 -2x = -2 Divide each side by '-2'. x = 1 Simplifying x = 1
| -2+2p=-14 | | 13y+(4y)(3x)+x= | | 5x+15=15-3x+9 | | 4y-6=-22 | | 2(x-4)+3=4x+7 | | 6x^2+47x+92=0 | | (2x+28)=(3x+137) | | -24-7n=-8(3-6n) | | 42=3(2-3n)-6 | | -19=3(7+3n)+8(8n-5) | | 180=111-u | | -12+19/-7= | | -12+-42/-7= | | 60x^2-20x+1=0 | | 84=2w+2L-3 | | 15y-11y=20 | | -12+-126/-7= | | x^2+(x*y)=120 | | 84+3x=1x | | -9u-5+6=19 | | -12+h/7=6 | | -a+5+6a=1+5a+3 | | -12+h/7= | | 8x+4(2-3x)=36-6x | | (4x-3)+3(3x+6)=5x-1 | | 4x^3-33x^2-30x=0 | | 2x+17+3x-4=180 | | 32=2x+14 | | 0.625=-0.50x | | 88+1.5h=94+2h | | 85=3(x-1)+8x | | -5(k-1)-(-6k+1)=9 |